Intercropping of short- and tall-stature maize decreases lodging risk without yield penalty at high planting density - Ren, Jianhong; Wei, Dejie; Zhang, Xinru; Wu, Cai; Han, Wenwen; Shi, Lingxin; Tang, Zhiyi; Wu, Zhihua; Liu, Guangzhou; Cui, Yanhong; Du, Xiong; Gao, Zhen (Frontiers in Plant Science, 2025)
High planting density of maize usually results in higher grain yield but also raises the risk of lodging. Cultivar intercropping had been proved to improve yield and stress resistance. Thus, we aimed to coordinate grain yield and lodging resistance of maize under high planting density by intercropping short-stalked Zhengdan958 (ZD) with tall-stalked Xianyu335 (XY). Five planting systems were conducted, i.e. SZD: sole Zhengdan 958 at normal density (7.5 plants m-2); SXY and SHXY: sole Xianyu 335 at normal and high density (9.0 plants m-2); IND and IHD: normal density ZD intercropped with normal and high density XY, respectively. Land equivalent ratio (LER) averaged to 0.99 and 0.96 in two experimental years, indicating no land use advantage of maize variety intercropping compared to monocultures. The average relative yield (partial LER) of ZD was 0.36-0.42, but that of XY was 0.54-0.63, indicating dominance of tall XY in the intercropping. Yield of intercropped XY per meter row was 13.3% and 17.0% higher than sole XY in two years; however, yield of intercropped ZD in IND and IHD was 16.7% and 25.3% lower than sole ZD in this study, respectively. Compared with IND, IHD did not significantly improve the population yield. The upper leaf area of intercropped XY was greater than sole stand, leading to increased interception of photosynthetically active radiation (PAR). However, the increased leaf area of intercropped XY resulted in reduced PAR for ZD, especially at the middle layer where assimilates are directly transported to the ear. Moreover, decreased superoxide dismutase (SOD) activity and SPAD, increased malondialdehyde content of ear leaf was observed for intercropped ZD, due to shading stress caused by tall XY. The principal component analysis indicated upper and middle leaf area, light interception, and SOD were closely related to grain yield. Lodging rate of sole XY under normal and high density was 4.3% and 22.0% in 2021, but lodging was absent for ZD and intercropped XY, which demonstrated that the lodging resistance of intercropped XY was significantly enhanced. This study presents a strategy to enhance maize lodging resistance without yield penalty or requiring additional inputs.